1996
DOI: 10.1111/j.1365-2621.1996.tb12204.x
|View full text |Cite
|
Sign up to set email alerts
|

Salt, Cryoprotectants and Preheating Temperature Effects on Surimi‐like Material from Beef or Pork

Abstract: Gel forming ability, measured by cooked gel hardness, and water-holding capacity of surimi-like pork were enhanced by addition of NaCl at 1.5 or 3% although 4.5% or 6% NaCl did not further increase hardness. Cooked gel strength was unaffected by freezing of beef or pork surimilike materials for 48 hr. Addition of cryoprotectants (3% or 6% sorbitol, 3% glycerol, or 3% sucrose) before freezing had no effect on gel forming ability. Gel hardness was not increased by preheating prior to cooking. Preheating surimi-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 30 publications
1
14
0
1
Order By: Relevance
“…Salt also increases dissociation of actomyosin through physical cuts or tears of the muscle fibers during comminuting. The dissociated myosin participates in gel matrix formation and binds water (Park and others 1996). The greatest gelling effect of Pacific whiting surimi at neutral pH was obtained at 2.5% NaCl among the salt concentrations tested between 0% and 2.5% (Chung and others 1993).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Salt also increases dissociation of actomyosin through physical cuts or tears of the muscle fibers during comminuting. The dissociated myosin participates in gel matrix formation and binds water (Park and others 1996). The greatest gelling effect of Pacific whiting surimi at neutral pH was obtained at 2.5% NaCl among the salt concentrations tested between 0% and 2.5% (Chung and others 1993).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to covalent dipeptide (lysine and glutamic acid) linkages, which were initiated by endogenous transglutaminase, intermolecular hydrophobic interactions probably contributed to the low temperature setting reaction (Lanier 2000). Setting induces conformational changes in the protein molecules by localized exposure and subsequent interaction of hydrophobic amino acid residues, resulting in the formation of a stronger gel (Park and others 1996). The requirement of salt addition to surimi paste for inducing setting also supports the role of hydrophobic interactions because certain salts, such as sodium chloride, act with water molecules to strengthen the hydrophobic interactions between proteins (Lanier 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Modified procedure of Park, Brewer, McKeith, Bechtel, and Novakofski (1996) was followed. Jars of frozen mixed gels were tempered and 2 g of SSP/sugars (0, 4, 8, 12%, w/w; XOS, Tre, Sor, Suc) mixed gels were dissolved in 0.6 M NaCl/0.05 M sodium phosphate buffer (pH 7.0) with gentle stirring for 1 h at 4°C.…”
Section: Protein Solubilitymentioning
confidence: 99%
“…In fish surimi, cryoprotectants are usually added to protect the functionality of surimi protein (Lee, 1990). Park et al (1996) showed that addition of cryoprotectants prior to freezing had no protective effect on gel-forming ability of surimi-like materials prepared from beef or pork skeletal muscles. Other researchers (Park et al, 1993) have reported that cryoprotectants had marked positive effects on protein solubility and gelation properties of minced beef.…”
Section: Introductionmentioning
confidence: 99%